Biliary Strictures: A Surgeon's Perspective for Interventional Radiologists - Katariya, Nitin; Mathur, Amit K. (Seminars in Interventional Radiology, 2021)
Biliary strictures can be a challenging clinical problem to manage and often have unclear etiologies, including benign and malignant causes. Left untreated, these problems can lead to significant morbidity and mortality linked to their underlying diagnosis. The approach to adult patients with biliary strictures requires a multidisciplinary team involving surgeons, interventional endoscopists, and interventional radiologists for diagnosis, symptom relief, palliation, as well as potential curative management. From a surgeon's perspective, there are many ways to classify and approach these strictures. It is of paramount importance to start with an excellent understanding of the patient's prior surgical history. In approaching a patient with a new diagnosis of biliary stricture, it is also critical to understand its etiology relatively quickly, as 70% are malignant in the adult population. Concurrently, one must clearly define the location and extent of the stricture: intrahepatic, hilar, or distal extrahepatic bile duct, as well as whether it is a singular lesion or multifocal phenotypes. This information provides a path forward in clinical decision-making regarding durability and efficacy of therapy, which is typically aimed at decompression and/or surgical resection to prevent cholangitis, sepsis, and progressive hepatic insufficiency.
Keywords: biliary stricture; cholangiocarcinoma; PTC; MRCP; ERCP; modified Hutson loop